2016
DOI: 10.3897/zookeys.559.6281
|View full text |Cite
|
Sign up to set email alerts
|

A black-and-red stick insect from the Philippines – observations on the external anatomy and natural history of a new species of Orthomeria

Abstract: A new stick insect of the genus Orthomeria Kirby, 1904 (Phasmatodea, Aschiphasmatidae) is described from the Philippines. Orthomeria (Orthomeria) kangi sp. n. is readily distinguished from all other congeners by the distinctive blood red colouration of the costal region of the hind wings. Major features of the external morphology of adults, eggs, and first-instar nymphs are illustrated. Locomotory attachment pads are of the smooth type with irregular microgrooves on the contact surface. An unusual condition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For example, the orb web spider Zygiella (Araneae, Araneidae) has serrate claws to move on a spider web efficiently (Foelix, 1996). The fishing spider, Dolomedes, uses such claws to break its locomotion on the water surface by interlocking with its dragline (Gorb and Barth, 1994), the stick insect Orthomeria (Phasmatodea, Aschiphasmatidae) has pectinate claws and often encounters heterogeneous plant surfaces including some covered with trichomes (Vallotto et al, 2016), and the bee louse Braula (Diptera, Braulidae) has tiny comb-like claws to attach to hairs on the honey bee thorax (Ellis et al, 2010).…”
Section: Discussion Attachment On Feathers and The Role Of Specializementioning
confidence: 99%
“…For example, the orb web spider Zygiella (Araneae, Araneidae) has serrate claws to move on a spider web efficiently (Foelix, 1996). The fishing spider, Dolomedes, uses such claws to break its locomotion on the water surface by interlocking with its dragline (Gorb and Barth, 1994), the stick insect Orthomeria (Phasmatodea, Aschiphasmatidae) has pectinate claws and often encounters heterogeneous plant surfaces including some covered with trichomes (Vallotto et al, 2016), and the bee louse Braula (Diptera, Braulidae) has tiny comb-like claws to attach to hairs on the honey bee thorax (Ellis et al, 2010).…”
Section: Discussion Attachment On Feathers and The Role Of Specializementioning
confidence: 99%
“…Most species possess one euplantula on each of the four proximal tarsomeres enabling adjustment to the surface profile. In some species, a fifth euplantula is found on the distal tarsomere as well (Vallotto et al, 2016). In contrast to the arolium, the euplantulae generate large friction coefficients, when they are pressed onto the substrate due to shear forces, but create negligible adhesion (Busshardt et al, 2011(Busshardt et al, , 2012Labonte and Federle, 2013;Labonte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Carausius morosus possesses comparatively long nubs (Busshardt et al, 2012), while other stick insects from different lineages bear shorter nubs (Beutel and Gorb, 2008;Gottardo and Heller, 2012;Büscher and Gorb, 2017). Some taxa possess entirely smooth euplantulae without any micromorphological ornamentation (Busshardt et al, 2012;Gottardo and Vallotto, 2014;Gottardo et al, 2015;Vallotto et al, 2016;Büscher and Gorb, 2017), and Dallaiphasma eximius revealed a hexagonal or plateau pattern (Gottardo, 2011). Although the structural diversity of phasmatodean AMs is known (Büscher et al, 2018) and the phylogenetic clustering of similar AMs is supposed to partly reflect the evolution of Phasmatodea (Gottardo et al, 2015;Büscher and Gorb, 2017), there is no recent study approaching the phylogenetic relationships of the different AMs.…”
Section: Introductionmentioning
confidence: 99%
“…Pictures available in Vallotto et al (2016) indicate that this difference is also observed between first instar nymph and adult of O. kangi, suggesting that a progressive increase in the fusion between metanotum and median segment tergite throughout post-embryonic development may be a widespread condition in Phasmatodea. In P. paulense, the first instar nymph also differs from the adult in general coloration of body, proportions between size of body segments, and (adult parenthetical): ocelli absent (present); antennae 9-segmented, scape cylindrical, distal flagellomere as long as previous four together (antennae with more than 40 segments, scape dorsoventrally compressed, distal flagellomeres much shorter than the median ones); abdomen dorsally with four longitudinal rows of sparse, short setae (absent).…”
Section: Morphological Remarksmentioning
confidence: 94%
“…First instar nymph of Orthomeria kangi Vallotto et al, 2016 (Aschiphasmatidae: Aschiphasmatinae) (Vallotto et al 2016) differs from the one of P. paulense on the color of the whole body and body parts and (P. paulense parenthetical): body setal vestiture dense, black and relatively long on all body and body appendages (scarce, yellowish and relatively short); pronotum apparently bulged (not bulged); mesonotum less than 2× longer than pronotum or metanotum (more than 2× longer); median segment longer than metanotum (slightly shorter); anterior femur straight (slightly curved proximately); posterior tibia arched (straight).…”
Section: Morphological Remarksmentioning
confidence: 99%